Faktor Keputusan Konsumen Dalam Memilih Obat Bebas Di Provinsi Dki Jakarta - Fenny Silviana Rizal; Ido Silviana Genesio; Natanael Silviana Nugroho; Nelson Pribady Lioe (Universitas Prasetiya Mulya, 2019)
Growth of Pharmaceutical Industry in Indonesia is still highly potential encouraged by high growth of population, increased health awareness, increased economic levels, and improved access & health budget . This research will help industry players who need to understand the market. According to random sampling data taken on July 2017, from 200 respondents aged 20 y.o. and above shows that the efficacy of drugs, the speed of drug reaction, and side effects of drug are the most important considered aspects, while the taste/sensation of drug and availability of gimmick for consumer are the most unimportant considered aspects in buying OTC drug.